(untitled) (Historia, 2022)
Book1: Daniel Terris, The Trials of Richard Goldstone Rutgers University Press, New Brunswick, 2019 367 pp ISBN 978-0-8135 9996-0, 38.95 (hardback). Book 2: Graham Viney, The Last Hurrah: South Africa and the Royal Tour of 1947 Johannesburg: Jonathan Ball, Johannesburg and Cape Town, 2018 xiv + 386 pp ISBN 978-1-86842-924-0, R285 (paperback).